Investigating amyloid beta‐induced toxicity in tau‐deficient human neurons: Developing topics. (7th December 2020) - Ng, Bryan; Vowles, Jane; Cowley, Sally A; Caffrey, Tara M; Connor‐Robson, Natalie; Wade‐Martins, Richard
Abstract: Background: Amyloid‐b (Ab) and tau aggregates are two major pathological hallmarks and known to be dysregulated in Alzheimer's disease (AD), leading to widespread aggregation. We now know from tau‐deficient animal models that tau does not merely facilitate Ab‐induced toxicity but is also essential in that particular toxic cascade. However, a tau‐deficient human in vitro model has not been available to corroborate these studies. Method: Here we generated the first MAPT ‐/‐ human induced pluripotent stem cell (iPSC) lines with CRISPR‐Cas9‐mediated genome editing in order to study the effects of tau deficiency in human biological context. We also established a versatile and scalable cortical neuron differentiation protocol which successfully produced a heterogeneous population of functional neurons manifesting cortical identity in co‐culture with rat astrocytes. Furthermore, we extracted brain homogenate from an AD patient to serve as the source of extrinsic Ab in addition to synthetic Ab oligomers. Result: iPSC‐derived MAPT ‐/‐ cortical neurons exhibited lower firing amplitude and frequency compared to MAPT +/+ neurons at baseline, while expressing similar number of synapses. On the other hand, MAPT ‐/‐ neurons demonstrated impaired axonal outgrowth over 5 days of live imaging. Upon extrinsic AD brain homogenate and/or Ab1‐42 oligomer insults, MAPT ‐/‐ neurons appeared to be protected from axonal degeneration, cytotoxicity and hyperactivation as compared to MAPT +/+ neurons. However, the MAPT ‐/‐ background was unable to prevent Ab‐induced loss of synapses. Conclusion: Taken together, the absence of tau in human neurons resulted in phenotypic changes at baseline and could result in neuroprotection in MAPT ‐/‐ neurons from Ab‐induced toxicity.